PERUMUSAN STRATEGI PADA TAMAN REKREASI SELECTA BERDASARKAN ANALISIS INTERNAL DAN EKSTERNAL PERUSAHAAN - Lucia Putri Yuliana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
Strategy Formulation for Selecta Recreation Park based on Company’s Internal and External AnalysesEach company should understand internal and external conditions surrounding its establishment. Sharp competition in tourism industry had urged Selecta Recreation Park to formulate its competitive strategy to maintain business existence. The objective of this research is to understand internal and external conditions of Selecta Recreation Park based on IFE (Internal Factor Evaluation) and EFE (External Factor Evaluation), to recognize the position of Seleta Recreation Park based on results of SWOT (Strengths-Weaknesses-Opportunities-Threats)analysis and IE (Internal-External) Matrix, and to find out the proper strategy for Selecta Recreation Park that helps it to complete other tourism objects in Batu City. IFE (Internal Factor Evaluation) analysis was used to recognize the most influential strengths and weakness to the company. EFE (External Factor Evaluation) analysis was performed to comprehend the most influential opportunities and threats to the company. Both analyses were using SWOT (Strengths-Weaknesses-Opportunities-Threats) Analysis and IE Matrix. IFE and EFE nalyses were processing the data, and had found that Selecta Recreation Park in the position of hold and maintaining. Matrix analysis of QSPM (Quantitative Strategic Planning Matrix)was then employed to determine the most appropriate strategy alternative for Selecta Recreation Park, and the analytical result indicate that the most interactive and the most appropriate strategy alternative strategy was product development strategy, which involved increasing product diversity and also bringing the innovation into products and facilities available to consumers.Keywords: Selecta Recreation Park, Strategy Formulation, Internal and External Conditions